2021
DOI: 10.1007/s10615-021-00809-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Evidence-Based Learning Theories to Guide the Development of Virtual Simulations

Abstract: Technology-enhanced training such as virtual simulations can be effective only to the extent evidence-based principles of learning are integrated into their training platforms. Assuming skill acquisition is the target of training, programs should include time and space for repeated practice opportunities structured through evidence-based learning theories (Amodeo et al. in Adm Soc Work 33:423–438, 2009). Essential learning attributes derived from Cognitive Load Theory (Sweller in Cognit Sci 12:257–285, 1988) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…When a theory was utilised to evaluate the simulation-based experience, student performance was greater despite no difference in knowledge to a control group [ 33 ]. Previous researchers have suggested that the use of a learning theory within simulation-based education and training provides a more structured experience that integrates effective learning attributes and skills [ 51 ]. Greater use of learning theories in the development of moulage interventions may improve outcomes for learners beyond experience.…”
Section: Discussionmentioning
confidence: 99%
“…When a theory was utilised to evaluate the simulation-based experience, student performance was greater despite no difference in knowledge to a control group [ 33 ]. Previous researchers have suggested that the use of a learning theory within simulation-based education and training provides a more structured experience that integrates effective learning attributes and skills [ 51 ]. Greater use of learning theories in the development of moulage interventions may improve outcomes for learners beyond experience.…”
Section: Discussionmentioning
confidence: 99%
“…Though VR represents an established technology with a history of commercially available headsets that began in the late 1970s and early 1980s, social work has yet to fully incorporate VR technology that can be harnessed to enhance the workforce's training [22]. With the increasing prevalence of VR and decreasing costs, VR is making inroads into the social sciences, including child welfare [23]. Institutions such as Stanford's Virtual Human Interaction Lab (https://www.stanfordvr.com/projects/ accessed on 1 July 2021), the University of Southern California's (USC) Institute of Creative Technology (https://ict.usc.edu/ accessed on 1 July 2021), and the University of Utah's Virtual Social Work Trainer (https://vswt.utah.edu/ accessed on 1 July 2021) are investigating prosocial uses for VR as a novel approach to training.…”
Section: Leveraging Technologymentioning
confidence: 99%
“…Based on the experiences of professional domains that have utilized VR extensively, and our own experiences developing an initial prototype specific to child welfare, realizing the benefits of VR to increase the effectiveness of child welfare workers requires attention on several important aspects. Such aspects include being developed based on evidence-based learning theories [23], or else VR will simply represent more technology for technology's sake. In other words, merely using VR does not ensure learning [27].…”
Section: Leveraging Technologymentioning
confidence: 99%
“…These technologies are being researched and implemented in different domains, such as medical training, commercial VR, collaborative and remote workspaces, rehabilitation, and serious games [7]. Cognitive load is one of the most effective types of data fueling self-adaptive technologies [9], [12]- [16]. This project is built on the same perspective with the feedback loop depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%